Dopad čitateľstva mladých generácií na kultúrny prenos v lokálnych spoločenstvách - Murín, Ivan (Lidé města, 2026)
In local populations – which often have fewer formal learning opportunities than complex urban centers – reading serves as a vital tool for information acquisition, deeply tied to the evolution of literacy, education, and cultural context. Historically, general literacy and the associated competencies of the population developed only gradually. It was not until the second half of the 20th century that reading emerged as a preferred activity and a primary form of individual and social learning. By providing a window into the wider world, reading allowed rural inhabitants to access distant information with significantly less effort and lower “interpretative” risk than traditional local sources provided. As reading became integrated into local culture, it was supported by the establishment of school, public, and family libraries, as well as reading clubs. The spread of readership facilitated a significant “import” of cultural innovation, markedly increasing individual cultural capital and the overall vitality of local populations. What began as a narrow transfer of information has evolved into a robust opportunity to educate the youngest generation, particularly schoolchildren, through local initiatives that support and sustain their reading habits.